Implementation of palliative care educational intervention in long-term care: a qualitative multi-perspective investigation. (2nd January 2020) - Frey, Rosemary; Balmer, Deborah; Boyd, Michal; Robinson, Jackie; Gott, Merryn
ABSTRACT: In industrialised countries, a large number of older adults with increasingly complex end of life care needs will die while in long-term care. It is essential that processes be in place to facilitate quality end of life care in these settings. In collaboration with two local hospices over the course of one year, we developed a new model of palliative care within long-term care – Supportive Hospice Aged Residential Exchange (SHARE). SHARE fostered knowledge exchange between hospice nurses and long-term care staff to improve palliative care delivery within 20 long-term care facilities (LTCF's). An in-depth qualitative investigation of the views of 59 healthcare professionals and 12 bereaved family members of residents, regarding SHARE implementation, was undertaken through semi-structured interviews. Transcripts were analysed thematically and mapped to the theoretical domains framework (TDF) in order to identify facilitators and challenges to SHARE implementation. Domains facilitating SHARE implementation provided benefits in terms of 'knowledge', 'skills development', and supported the mentoring and role modelling provided by the hospice. Challenges highlighted the resource constraints of the long-term care context. The use of the TDF has enabled the identification of essential components such as skills development, which facilitate the implementation of SHARE in LTCF's.